System optimization of steam generation in the dual-flash compound circulation system - Hao, Zhang; Yanting, Zhang; Lin, Wang; Jingyu, Xu; Zheng, Huang; Guangzhi, Zhang; Yunlong, Zheng (Frontiers in Energy Research, 2023)
Concentrating on the problem of massive energy loss in the compressor, expansion valve, and the other components present in the high-temperature heat pump system under extensive temperature lift, the dual-flash compound circulation system is proposed to improve the thermodynamic performance of the system. According to the relationship between the different parameters in the system and the refrigerant displacement of the two compressors, the thermodynamic model of the dual-flash compound circulation system was established. As the complex system structure consists of the characteristics of many variable parameters, the article combines the multivariate simulated annealing algorithm, utilizes the system COP as the optimization goal, and completes the calculation of the thermodynamic parameters in the steady-state of the system that is based on satisfying the conditions of the system process. Using R245fa as the refrigerant, the condensation temperature is set within the range of 110 ℃ to 140 ℃ for the model calculation. The results show that, compared to the traditional two-stage compression system under the same environment, the COP of the dual-flash compound circulation system can be increased up to 5.71% to 12.13%, and the exergy efficiency can be increased by 5.11% to 10.71%, respectively. Besides, steam production per unit refrigerant is also increased by 3.79% to 5.14%. Finally, the feasibility of the theoretical model is verified by simulation, and it is concluded that the dual-flash compound circulation system has better steam production performance at the extensive temperature lift and the elevated condensation temperature.